2014
DOI: 10.1186/1471-2407-14-93
|View full text |Cite
|
Sign up to set email alerts
|

PKC α regulates netrin-1/UNC5B-mediated survival pathway in bladder cancer

Abstract: BackgroundNetrin-1 and its receptor UNC5B play important roles in angiogenesis, embryonic development, cancer and inflammation. However, their expression patttern and biological roles in bladder cancer have not been well characterized. The present study aims to investigating the clinical significance of PKC α, netrin-1 and UNC5B in bladder cancer as well as their association with malignant biological behavior of cancer cells.MethodsNetrin-1 and UNC5B expression was examined in 120 bladder cancer specimens usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…Compared to normal adjacent tissues, netrin-1 expression level was significantly higher in TCC tumors ( Fig. 1A-B), and significantly associated with the high tumor stage ( Supplementary Table 1), consistent with our previous observations on a cohort of 160 primary TCCs [17]. At mRNA level, netrin-1 expression levels were remarkably higher in the high-grade (Mann-Whitney U Test, low-grade vs. high-grade, P = 0.027, Fig.…”
Section: High Expression Of Netrin-1 Predicts a Poor Prognosis Of Tccsupporting
confidence: 91%
“…Compared to normal adjacent tissues, netrin-1 expression level was significantly higher in TCC tumors ( Fig. 1A-B), and significantly associated with the high tumor stage ( Supplementary Table 1), consistent with our previous observations on a cohort of 160 primary TCCs [17]. At mRNA level, netrin-1 expression levels were remarkably higher in the high-grade (Mann-Whitney U Test, low-grade vs. high-grade, P = 0.027, Fig.…”
Section: High Expression Of Netrin-1 Predicts a Poor Prognosis Of Tccsupporting
confidence: 91%
“…Recent studies have reported that PKC can promote the proliferation, differentiation and migration of bladder cancer cells. Thus, PKC is closely related to the biological behaviors of bladder cancer (37). Through our experiments, we found that isoquercitrin significantly reduced the expression level of phosphorylated PKC.…”
Section: Isoquercitrin-mediated Cell Cycle Arrest Of Bladder Cancer Cmentioning
confidence: 59%
“…The UNC5B receptor is down-regulated in bladder cancer tissues and is associated with bladder cancer recurrence [10]. Therefore, we hypothesized that UNC5B signaling plays a key role in the development of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Receptors of netrin-1 include DCC, the UNC5H family of proteins (UNC5A, UNC5B, UNC5C, and UNC5D) and neogenin [9]. In-depth studies of UNC5B in tumors have revealed that UNC5B is down-regulated in bladder cancer tissues and that lower UNC5B expression is an independent determinants for recurrence of bladder cancer [10]. These findings suggest that UNC5B may function as a tumor suppressor in bladder cancer.…”
Section: Introductionmentioning
confidence: 99%